Kecukupan Asupan Zinc Berhubungan dengan Perkembangan Motorik Pada Balita Stunting dan Non-Stunting - Hesty Dwi Septiawahyuni; Dewi Retno Suminar (Amerta Nutrition, 2019)
Background: One Indicator of successful health development are toddlers free from stunting. The cause of stunting is a lack of macro and micro nutrients and chronic infectious diseases. Micronutrients such as zinc have  a role in growth which affects the  hormones that play a role in bone growth. The role of zinc in motoric development indirectly is in arranging  and releasing neurotransmitters that can affect nerve stimulation in the brain. This neurotransmitters will deliver nerve stimulation so that motor motion occurs. Motor development is a motion that involves muscles, brain and nerve that are controlled by the central part of the motor that is brain. Objectives: The purpose of this study was to analyze the relationship between adequacy of zinc intake and motoric development in stunted and non-stunted toddlers.Methods: This type of research is an observational study with cross sectional design. The sample size was 50 toddlers, consisted of 25 stunting toodlers and 25 non-stunting toddlers and lived  in Puskesmas Wilangan, Nganjuk District, chosen by simple random sampling technique. Adequacy of zinc intake data was assessed using the Food Recall Form 3x 24 hours. Measurement of motoric development using the Pre-Screening Development Questionnaire (KPSP). Descriptive and inferential data analysis using Chi Square Test. Results: The result showed that there was a correlation between the level of zinc adequacy and motor development in the stunting toddler group (p=0.04) and non-stunting toddlers group (p=0.031).Conclusions: The level of adequacy of zinc has enough motor development better than the level of zinc sufficiency is less in the group of non-stunting toddlers.ABSTRAKLatar Belakang: Salah satu indikator keberhasilan pembangunan kesehatan adalah balita  terbebas dari stunting. Penyebab stunting yaitu kekurangan zat gizi makro maupun mikro dan penyakit infeksi kronis. Zat gizi mikro seperti zinc mempunyai peran pada pertumbuhan yaitu mempengaruhi hormon-hormon yang berperan dalam pertumbuhan tulang. Selain itu, peran zinc pada perkembangan motorik secara tidak langsung yaitu dalam menyusun dan melepas neurotransmitter yang dapat mempengaruhi rangsangan syaraf di dalam otak. Neurotransmitter ini akan menghantarkan rangsangan syaraf sehingga gerak motorik terjadi. Perkembangan motorik merupakan gerak yang melibatkan otot, otak dan syaraf yang dikontrol pada bagian pusat motorik yaitu otak.Tujuan: Tujuan penelitian adalah untuk menganalisis hubungan kecukupan asupan zinc dengan perkembangan motorik pada balita stunting dan non-stunting.  Metode: Jenis penelitian tergolong penelitian observasional dengan desain cross-sectional. Sampel penelitian berjumlah 50 balita, terdiri dari 25 balita stunting dan 25 balita non-stunting yang bertempat tinggal  di wilayah kerja Puskesmas Wilangan Kabupaten Nganjuk, dipilih dengan teknik simple random sampling. Data kecukupan asupan zinc dinilai menggunakan formulir Food Recall yang dilakukan 3x24 jam. Pengukuran perkembangan motorik menggunakan Kuesioner Pra Skrining Perkembangan (KPSP). Analisis data secara deskriptif dan Inferensial menggunakan uji Chi Square.Hasil: Hasil penelitian menunjukkan terdapat hubungan antara tingkat kecukupan zinc dengan perkembangan motorik pada kelompok balita stunting (p=0,04) dan kelompok balita non-stunting (p=0,031).  Kesimpulan: Tingkat kecukupan zinc cukup mempunyai perkembangan motorik yang lebih baik daripada tingkat kecukupan zinc kurang pada kelompok balita non-stunting.